Infant, child and adolescent nutrition : a practical handbook - More, Judy (London CRC Press, 2021)
"This Second Edition is an evidence-based, practical guide which provides readers an introduction introduces readers to the theory behind optimal child nutrition. Containing practical advice on how to put that theory into practice, this new edition facilitates learning through case studies, key points, and learning activities. Divided into seven sections, chapters cover prenatal nutrition and nutrition throughout childhood from preterm babies to adolescents up to the age of 18. It serves as a useful reference for individuals responsible for the nutritional health of children in primary care and community settings"--
Includes bibliographical references and index.
Keywords: Children -- Nutrition; Infants -- Nutrition; Teenagers -- Nutrition